2006
DOI: 10.1007/s11136-006-0063-3
|View full text |Cite
|
Sign up to set email alerts
|

Condensation and validation of a 4-item index of the Acne-QoL

Abstract: The Acne-Q(4) is accurately reflective of the parent instrument and may facilitate the psychometric evaluation of the impact of facial acne on patients in routine clinical practice by its practicality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…Such patientcentric measures are routinely included as a complement to clinician-based global acne severity assessments in clinical trials. [20][21][22][23][24][25] Future researchers may wish to evaluate whether clinicians who do not conduct research would find the inclusion of patient experiences useful for an ideal acne severity scale.…”
Section: Discussionmentioning
confidence: 99%
“…Such patientcentric measures are routinely included as a complement to clinician-based global acne severity assessments in clinical trials. [20][21][22][23][24][25] Future researchers may wish to evaluate whether clinicians who do not conduct research would find the inclusion of patient experiences useful for an ideal acne severity scale.…”
Section: Discussionmentioning
confidence: 99%
“…1 In our modeling of Acne-QoL determinants, the rank order of factors was clinical severity, duration of acne, gender, and age. Previous studies have shown that the correlation of clinical grading and QoL measures has been either weak or none, depending on whether the QoL instruments used were specific 1,3,7,11 or more general, respectively. [12][13][14] Our findings concur with the concept that these two measures are complementary but dissimilar.…”
Section: Discussionmentioning
confidence: 99%
“…The relevant questions relate to dissatisfaction with appearance, feeling upset, concern about meeting new people, and concern about scarring. 11 In addition to providing a patient-centered perspective, disparate QoL scores may assist clinicians in identifying patients at risk of psychiatric disturbances, such as depression or body dysmorphic disorder. Subsequent management of such patients will then appropriately require prioritization to focus therapy primarily on acne, the psychiatric disorder, or both concurrently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acne is a disease that can have negative consequences on the patients' psyche, which can cause depression and loss of self-esteem with important effects on their social life [11,12,13,14,15]. Since acne is a chronic disease, it typically requires prolonged treatment.…”
Section: Discussionmentioning
confidence: 99%